Retention of castings fabricated by plastic coping and direct wax up for single crown and bridge in different implant systems - Mahmod Kazemi; Alireza Pornasrollah; Somayeh Allahyari; Hamid Jalali (Tehran University of Medical Sciences, 2015)
Background and Aims: Adequate retention has significant importance in the prognosis of implant supported cemented the restorations. Limited literature had evaluated the effect of direct wax up or use of plastic coping on the retention of these restorations. This aims of this study was to compare the retention of castings fabricated by the plastic coping and direct wax up for single crown and bridge in three implant systems.   Materials and Methods: 28 specimens of each implant systems were randomly divided into 4 groups. Groups included wax patterns for single crowns and bridges that were made from plastic coping or direct wax up. All the wax patterns were invested and casted with base metal alloy, in similar conditions. After castings were cemented to the related abutments, the specimens were subjected to a pull out force in a universal testing machine at a cross head speed of 0.5 mm/min. The load required to decement each casting was recorded and the mean values for each group were calculated. Data were analyzed using three-way ANOVA.   Results: Comparing the between systems in crowns fabricated from plastic coping, there was no significant difference between Replace and Implantium (P=0.124), but ITI had significantly lower values than that of other systems (P<0.001 Comparing the systems in crowns fabricated from direct wax up, Implantium had the greatest retention and ITI had the lowest retention (P<0/001). Comparing the bridges with both method, Replace had the greatest retention and ITI had the lowest retention.   Conclusion: Implantium and Replace system exhibited the highest retention for fabricating crowns, and bridges, respectively.